PERMAINAN KARTU SEBAGAI MEDIA PROMOSI NOVEL: JAKARTA THE GOLDEN RULE - Nindyaswari, Khansa Nabila; Akbar Pahala, Agam (Program Studi Pendidikan Seni Rupa FBS UNJ, 2024)
The artist's concern about sales in previous novels became the background for the creation of a card game entitled